Specific approaches to patients affected by dementia and covid-19 in nursing homes: the role of the geriatrician - Veronese, Nicola (Ageing Res Rev, 2021)
The coronavirus disease 19 (COVID-19) is relevant in older people. Attention was given to the nursing homes in which frailer people are usually admitted. In this review, we discuss the approaches for daily problems found in nursing home as geriatricians and potentially new research directions. We start with the problem of the older people affected by dementia and Behavioral and Psychological Symptoms of Dementia for which also the execution of a simple diagnostic test (such as nasopharyngeal swab) could be problematic. Another important problem is the management of wandering patients for which the re-organization of the spaces and vaccination could be the solutions. The relationship with families is another important problem, also from a medico-legal point of view, that can be faced using video conferencing tools. Moreover, we discussed the importance of stratifying prognosis in older nursing home residents for the best management and therapeutically approach, including palliative care, also using telemedicine and the inclusion of prognostic tools in daily clinical practice. Finally, we approached the therapeutical issues in older people that suggests the necessity of future research for finding older-friendly medications.